2021
DOI: 10.5455/njcm.20210625054326
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress among Adolescent School Students in Hubli: A Cross-Sectional Study

Abstract: Background: Psychological morbidity in children and adolescents is high. The present study was done to assess the level of perceived stress and psychological morbidities among secondary school students. Methods: A cross-sectional study was done on 311 adolescent students in 9th and 10th classes of two government and two private schools in Hubli city, Karnataka. A validated and culturally adapted version of the 12-item general health questionnaire (GHQ-12) and perceived stress scale (PSS-10) was administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
2
1
Order By: Relevance
“…Second, perceived stress showed moderate to high positive correlations with the GHQ-12 total score and three subscales, further supporting the criterion validity of GHQ-12. These findings were consistent with previous studies ( Örücü and Demir, 2009 ; Gajula et al, 2021 ). It is thought that psychosocial stressors, such as living alone, social restrictions and isolation, financial burden, and loss of family members, that lead to heightened anxiety, fear, and anger, made a significant contribution to the higher level of stress experienced by patients with COVID-19 ( Torales et al, 2020 ; Matalon et al, 2021 ; Varman et al, 2022 ).…”
Section: Discussionsupporting
confidence: 94%
“…Second, perceived stress showed moderate to high positive correlations with the GHQ-12 total score and three subscales, further supporting the criterion validity of GHQ-12. These findings were consistent with previous studies ( Örücü and Demir, 2009 ; Gajula et al, 2021 ). It is thought that psychosocial stressors, such as living alone, social restrictions and isolation, financial burden, and loss of family members, that lead to heightened anxiety, fear, and anger, made a significant contribution to the higher level of stress experienced by patients with COVID-19 ( Torales et al, 2020 ; Matalon et al, 2021 ; Varman et al, 2022 ).…”
Section: Discussionsupporting
confidence: 94%
“…Second, perceived stress showed moderate to high positive correlations with the GHQ-12 total score and three subscales, further supporting the criterion validity of GHQ-12. These findings were consistent with previous studies (Örücü and Demir, 2009;Gajula et al, 2021). It is thought that psychosocial stressors, such as living alone, social restrictions and isolation, financial burden, and loss of family members, that lead to heightened anxiety, fear, and anger, made a significant contribution to the higher level of stress TABLE 4 The correlation between GHQ-12 subscales and their correlations with sleep quality, perceived stress, and daily functioning.…”
Section: Discussionsupporting
confidence: 90%
“…Gajula M et al, in their study on adolescent school students in India, reported higher proportion of students in high stress (24.44%). 17 We found no significant difference with respect to stress and sex of students. Gupta K et al reported similarly.…”
Section: Discussioncontrasting
confidence: 52%